LIQUEFACTION RISK ASSESSMENT BY THE USE OF GEOPHYSICAL TECHNIQUES: THE TEST AREA OF NAFPLION CITY, GREECE - Karastathis, V.K.; Karmis, P.; Novikova, T.; Roumelioti, Z.; Gerolymatou, E.; Papanastassiou, D.; Liakopoulos, S.; Giannoulopoulos, P.; Tsombos, P.; Papadopoulos, G.A. (Bulletin of the Geological Society of Greece, 2010)
An efficient and cost effective site characterization, with regard to the seismic hazard and liquefaction risk assessment, was accomplished with the aid of geophysics in the area, where the Nafplion city of Greece is expanding. The methodology adopted includes the recognition of the possible earthquake sources of the wider region, their modelling, in order to stochastically simulate the strong ground motion at the investigation area, and finally the calculation of the liquefaction risk. The investigation area was suspected of high liquefaction potential since the foundation ground consists of loose sandy silt with very shallow aquifer. The geophysical techniques considerably contributed to the detection and characterization of possible local seismic faults with the implementation of gravity and seismic methods. Special emphasis was given to the seismic depth migration and particularly to the construction of valid velocity models, in order to precisely calculate the dips of the possible faults. Additionally the geophysical techniques provided the near surface velocity structure for the calculation of the amplification of the seismic motion up to the surface, also required for the final estimation of the liquefaction risk. The seismic methods (seismic reflection, seismic refraction, seismic modelling, MASW, multichannel analysis of microtremors and crosshole investigations), if combined with geo-technical borehole testing, enhance their reliability and cover large areas in a cost-effective way in comparison with the standard borehole tests. In Nafplion area, evidence was found for a low factor of safety against liquefaction at specific sites within the study area. The results show that liquefaction probability can reach 80% at some sites depending on selected earthquake scenario, mainly at depths between 5 and 10 meters. This should be considered as highly important information for making risk-based design decision in this region.